Surgical Site Infections Causes and the Burden of Staphylococcus Aureus in these Infections with their Antibiotic Susceptibility Pattern - Kannaiyan, Kavitha; Ragunathan, Latha; Venkatachalam, Kanniappan (Annals of Pathology and Laboratory Medicine, 2018)
Background: Surgical site infections (SSI) set hurdles in the healing course of a significant proportion of abdominal surgical patients and thus associated with excessive health care costs. Staphylococcus aureus remains the principal causative agent in these infections. Also the emergence of multidrug resistant bacterial strains further complicates the recovery course of the patients and thus adds burden to both the patients and the surgeon. The intention of this study is to evaluate the etiology of SSI, to establish the incidence of S aureus and to determine their antimicrobial susceptibility pattern in patients with SSI. Methods: A cross section study was done in Aarupadai veedu medical college in patients attending surgery outpatient department for SSI. Purulent material was collected either with syringe or 2 sterile swabs and was sent to the microbiology department. The sample was processed as per standard guidelines, identified and antibiotic susceptibility was done for S.aureus. Result: Among the 63 SSI patients, 50 (79.4%) were culture positive. The most frequently isolated organism was S aureus 23 (36.5%) isolates. Among them methicillin resistant S.Aureus (MRSA) was 9 (39.1%). Both Methicillin sensitive S.aureus (MSSA) and MRSA were all sensitive to linezolid and vancomycin. Majority of the isolates were sensitive to amikacin and clindamicin. Conclusion: Thus our study concludes S. aureus as the foremost etiological agent of SSI, and treatment is further complicated by emerging multidrug resistant MRSA where empirical therapy can be started with clindamicin, amikacin in moderate risk cases and linezolid, vancomycin in high risk cases.